Development of pilot batch and grade estimation of coils of steel grade S355MC at rolling mill "1700", PJSC "ILYICH IRON AND STEEL WORKS" - Kurpe, O. G.; Kukhar, V. V.; Shebanits, O.; Кухар, В. В. (НТУ «Дніпровська політехніка», 2018)
Purpose. Development of technology of hot rolling coils using thermo-mechanical controlledprocess forthewide-strip rolling mill and grade estimation of coils.Methodology. Technology was developed and the first batch was produced using thermo-mechanical controlledprocess and improvement in surface quality was achieved via air cooling to a certain temperature.Findings.There has been developed technology, and pilot batch of hot rolling coils (6×1500 mm, steel grade S355MC) has been produced usingthermo-mechanical controlledprocess (TMCP) forthewide-strip rolling mill 1700. The integrated technology for TMCP coil production (steel grade S355MC) has been firstly developed for the rolling mill 1700 in accordance with EN 10149-2. Air cooling for coils to 450°C after coiling has been firstly used in the developed technology, which provides for decrease in air scale and improvement of surface quality for the customers.
Keywords: thermo-mechanical controlled process; hot rolling coils; rolling force; temperature conditions; technology